Application of a finite element and boundary element coupling algorithm in pressure response of a fracture-vuggy gas reservoir. Issue 1 (2nd January 2019) - Zhang, Tao; Chen, Peng; Chen, Yan
Abstract: In carbonate reservoirs, multiple large-scale caves are controlled by some single wells. The fluid flowing law in the reservoir is complex, and the production performance is unclear, which restricts the highly effective development of these kinds of reservoirs. In this paper, Darcy flow is used to characterize the fluid flow outside the cave, and the Navier–Stokes equation is used to characterize the free flow of the fluid in the cave. Based on the Darcy flow and Navier–Stokes equations, a fluid flow mathematical model is established for carbonate gas reservoirs with multiple large-scale caves. Then, the Beavers–Joseph–Saffman boundary condition, the finite element and boundary element coupling algorithm are proposed for computing the bottom-hole pseudo-pressure. Subsequently, we establish the interpretation graph for a large-scale cave reservoir and analyse the influence of the reservoir parameters on the pseudo-pressure and pseudo-pressure derivative curves. The results showed the following: (i) the larger the radius of the cave, the larger the concave-convex amplitude of the bottom-hole pressure curve. (ii) For the bottom-hole pressure curve, the smaller the distance, the earlier the convex appears and the larger the concave-convex amplitude. The research results can improve the development effects of carbonate reservoirs with large-scale caves.